2018
DOI: 10.1093/humrep/dey020
|View full text |Cite
|
Sign up to set email alerts
|

‘Man Up’: the importance and strategy for placing male reproductive health centre stage in the political and research agenda

Abstract: Approximately 1 in 20 young men today have sperm counts low enough to impair fertility, whereas this may not have been the case historically. The cause(s) of such a decline in male reproductive health is unknown, despite it being a global health issue. Concomitantly, little progress has been made in answering fundamental questions in andrology or in developing new diagnostic tools or alternative management strategies to ICSI in infertile men. We advocate formulation of a detailed roadmap for male reproductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 41 publications
3
50
0
1
Order By: Relevance
“…It is widely appreciated that our reliance on semen analysis—either to diagnose male infertility or to assess a functional response to treatment of male infertility—is inadequate (Barratt et al, ). Assays proposed over the years to fill these needs have not demonstrated efficacy at prospectively predicting the clinical outcome of generating a pregnancy (Barratt et al, ), and are often found to correlate with the traditional semen analysis parameters (Aitken, ; Giwercman et al, ; Hazary, Chaudhuri, & Wishart, ; Zini et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is widely appreciated that our reliance on semen analysis—either to diagnose male infertility or to assess a functional response to treatment of male infertility—is inadequate (Barratt et al, ). Assays proposed over the years to fill these needs have not demonstrated efficacy at prospectively predicting the clinical outcome of generating a pregnancy (Barratt et al, ), and are often found to correlate with the traditional semen analysis parameters (Aitken, ; Giwercman et al, ; Hazary, Chaudhuri, & Wishart, ; Zini et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely appreciated that our reliance on semen analysis—either to diagnose male infertility or to assess a functional response to treatment of male infertility—is inadequate (Barratt et al, ). Assays proposed over the years to fill these needs have not demonstrated efficacy at prospectively predicting the clinical outcome of generating a pregnancy (Barratt et al, ), and are often found to correlate with the traditional semen analysis parameters (Aitken, ; Giwercman et al, ; Hazary, Chaudhuri, & Wishart, ; Zini et al, ). Prospective data presented here strongly demonstrate that the Cap‐Score, a measure quantifying the percentage of sperm that can capacitate and undergo acrosome exocytosis (Cardona et al, ; Moody et al, ; Ostermeier et al, ), successfully predicted low or high success at achieving pregnancy in three or fewer attempts at IUI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations